Study of hydration of sarcosine, formation of its zwitterion and their different oligomers in aqueous media: a Raman spectroscopic and theoretical study - Sharma, Poornima; Singh, Dheeraj K.; Gupta, Vineet; Asthana, B. P.; Mishra, P. C.; Singh, Ranjan K. (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
{Raman spectra of the biologically important molecule sarcosine (SAR) (C3H7NO2) were studied experimentally in aqueous solution at different concentrations. These spectra were also calculated theoretically using density functional theory (DFT) at the B3LYP/6-31 1++G(d,p) level. Further, all the observed normal modes were assigned through potential energy distribution (PED). Geometry optimization of SAR produced its three conformers with slightly different energies. The lowest energy conformer of SAR was selected for a systematic solvation study wherein different numbers of water molecules (nW
Keywords: DFT calculations; Hydration; Oligomer; Raman spectra; Sarcosine; Zwitterion

Advances in the experimental and theoretical understandings of antibiotic conjugated gold nanoparticles for antibacterial applications - Khandelwal, Puneet; Singh, Dheeraj K.; Poddar, Pankaj (ChemistrySelect, 2019)
The worldwide bacterial resistance to a wide range of antibiotics originates a global health concern and calls for the development of new antibacterial agents. Over the recent years, nanomaterials-based agents have been proven to be useful for the effective antibacterial applications. Notably, the gold nanoparticles (AuNPs) draw particular attention due to their biological inertness and easy surface functionalization. It is now established that the antibiotic functionalization on the AuNPs surfaces increases the antibacterial efficacy even towards the antibiotic-resistant bacterial cells. Moreover, the antibacterial efficacy can be further enhanced by photothermal therapy using antibiotic conjugated AuNPs. In this review article, we have reviewed the advances in the development of the synthesis methods of antibiotic conjugated AuNPs and gold nanoclusters, and their antibacterial efficacy. We have also discussed the developments in the theoretical understandings behind the interaction of antibiotic molecules with gold surface and its relation to the antibacterial activity. We believe that few parameters including the selection of antibiotic molecules, the method of its attachment to AuNPs, the purification of antibiotic conjugated AuNPs, and the quantification of conjugated antibiotic are crucial and needs to be properly addressed. Moreover, there are many other future directions discussed, for using antibiotic conjugated AuNPs more effectively for antibacterial therapy.
Keywords: Antibacterial; antibiotic; DFT calculations; gold nanocluster; Gold nanoparticle; multi-drug resistance; photo-thermal therapy

Imidazole/4,4 `-azopyridine bridging binuclear Ru(II) complexes: design, synthesis, bimolecular interactions and cytotoxicity against HeLa cell line - Khanvilkar, Priyanka; Dash, Soumya R.; Pulipaka, Ramadevi; Shirsath, Kavita; Devkar, Ranjitsinh; Chakraborty, Debjani (Journal of the Iranian Chemical Society, 2021)
Binuclear Ru(II)-arene complexes [(eta(6)-pcym)(Flq)Ru(mu-im/mu-azpy)Ru(Flq)(eta(6)-p-cym)]Cl (C1-C8) (cym = cymene; Flq = fluoroquinolones; im = imidazole; azpy = 4,4 ` azo pyridine) have been synthesized and characterized by elemental analysis, molar conductivity and various spectral techniques (ESI-MS, IR, UV-Vis and H-1-NMR). The geometry of the complexes was optimized by DFT calculations, which revealed a pseudo-octahedral coordination around each metal centre. Binding of the synthesized complexes with CT-DNA and BSA was studied spectroscopically, and it has been established that the presence of two hydrophobic planar arene moieties enhances the binding efficacies of the binuclear complexes to the macromolecules, compared to their mononuclear analogues. The results of competitive binding between C1-C8 and ethidium bromide (EB) towards DNA have shown that the complexes are able to displace EB from DNA-EB adduct and interact with DNA via intercalation. The complexes display cytotoxicity against the HeLa human cervical cancer cell lines with IC50 values in the range of 30.1-120.9 mu M.
Keywords: Binuclear ruthenium (II) complexes; BSA binding interactions; DFT calculations; DNA; Fluoroquinolones (FQs); HeLa human cervical carcinoma

Ultrasound assisted green protocol for the synthesis of quinoxaline based bisspirooxindoles: crystal structure analysis, enone umpolung, DFT calculations, anti-cancer activity, and molecular docking studies - Baddepuri, Sravanthi; Allaka, Bhargava Sai; Gamidi, Rama Krishna; Faizan, Mohmmad; Pawar, Ravinder; Basavoju, Srinivas (Synthetic Communications, 2023)
A series of novel quinoxaline based bisspirooxindolo-pyrrolizidines were synthesized through 1,3-dipolar cycloaddition under ultrasonication with shorter reaction time and good yields. The compounds were well characterized by various spectroscopic methods and finally single crystal X-ray diffraction method (4c, 4d). DFT energy calculations confirm the regioselectivity due to enone umpolung effect. The in vitro anti-cancer activity of the synthesized compounds (4a-s) shows that the compounds 4g and 4q exhibited good anti-cancer activity with IC50 values14.51 +/- 1.1 and 11.36 +/- 0.23 mu M against DU-145 prostate cancer cell line; and 16.78 +/- 0.95 and 14.28 +/- 0.64 mu M against Hela cervical cancer cell lines when compared to the standard anti-cancer drug doxorubicin (1.75 +/- 0.06 and 1.35 +/- 0.09 mu M). In silico molecular docking studies indicated that the synthesized compounds may serve as a potential lead for the further development of novel anti-cancer agents.
Keywords: Anti-cancer activity; bisspirooxindoles; DFT calculations; Hirshfeld surface; ultrasonication